Correlation of mast cell density, tumor angiogenesis, and clinical outcomes in patients with endometrioid endometrial cancer - Pokpong Pansrikaew (2018)
Background: Tumor angiogenesis has been demonstrated in several kinds of neoplasms. There is evidence that mast cells can produce many different chemical mediators with angiogenic properties. Since their specific role in female genital tract cancer has not been well understood, this study was conducted to determine correlations between among mast cell density, tumor angiogenesis, and clinical outcomes in patients with endometrioid adenocarcinoma of endometrium. Methods: Histologically, four-micrometer-thick haematoxylin and eosin stained slides of hysterectomy specimens were evaluated. Microvessels were highlighted by CD31 immunostaining and mast cells were stained with 0.1% toluidine blue. All clinicopathological characteristics were reviewed to determine their possible correlation to microvessel density and number of mast cells. Results: A total of 46 patients who underwent a complete staging surgery were eligible for this study. The median age was 55 years (range, 32-70 years) and the median follow-up was 27.0 months (range 3.6-83.8). Microvessels appeared to correlate to some extent with parity and the mean count was likely to be higher in women with non-menopausal status (p=0.07), advanced FIGO stage (p=0.09), and lymph node metastasis (p=0.08). However, there was no significant correlation between microvessel counts, mast cell density, and disease recurrence. Conclusion: Our data suggest that the number of microvessel counts and mast cell density do not affect clinical progression or recurrence of endometrioid endometrial cancer.